The thunderweapon in religion and folklore : a study in comparative archaeology - Blinkenberg, Christian (UK : Cambridge University Press, 2011)
Originally published in 1911, this book constitutes an archaeological survey of the thunder weapon and its significance in a variety of different cultures. Containing numerous illustrative figures and detailed information on sources, this book will be of value to anyone with an interest in archaeology, anthropology and human prehistory.
1. The thunderstone in ancient greece. 2. The Thunderstone in ancient italian religion and folklore. 3. The original form and age of the ideas. 4. Retrospect. 5.Sources of particulars.
Keywords: Thunder gods; Thunderstorms Mythology